The SARS-CoV-2 mutation landscape is shaped before replication starts - Masone, Diego Fernando (2022)
Mutation landscapes and signatures have been thoroughly studied in SARS-CoV-2. Here, we analyse those patterns and link their changes to the viral replication niche. Surprisingly, those patterns look to be also modified after vaccination. Hence, by deductive reasoning we identify the steps of the coronavirus infection cycle in which those mutations initiate.